Teaching Sepaktakraw by Developing a Motion Ball-Based Soccer Training Model - Aryadi, Dedi; Arini, Ira (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
The sepaktakraw game is a team sport played by 3 people. Mastery of sepaktakraw skills cannot be separated from mastery of specific game techniques, namely kickkick/service techniques. Kick-off/service is a unique technique used to start the game in the sepaktakraw game, so many people say kick-off/service is the most important in the sepaktakraw game. This research aims to determine the procedures and feasibility of developing a training model in extracurricular learning for sepaktakraw sports, which is research using the R&D research method (Research and Development type ADDIE. The method stages in this research are (1). Literary research, (2). Role, (3). Making, (4). Comparative test, (5). Observation, (6). Validity test by experts. Game expert validation test 86, 363% > 81.25% (excellent), media expert validation test 88.636% > 81.25% (excellent), small class trials, it was found that 86.75 > 80, namely the strong category, and large class trials, it was found that 83.44 > 80 strong category. Based on the results of game expert validation tests, media expert validation tests, small class trials, and large class trials, it can be concluded that developing a motion ball-based soccer training model is suitable for use as a training model in sepaktakraw learning.